Enriched numerical manifold method with closed-form solutions for the crack-tip singularity in elastic fracture - Hua-rui ZHU; Hong ZHANG; Xi-long LI; Wei WU; Sun-jun HU; Gen-hua SHI (Computers and Geotechnics, 2026)

Cerrena unicolor laccases as sustainable biocatalysts for detoxifying hazardous long-chain phthalates and deconstructing plastic mulch films - Long-Bin Zhang; Jun Kang; Xiu-Gen Qiu; Zhou Cui; Yu-Tian Li; Yan Zheng; Yu Li; Yi Guan; Juan-Juan Yang; Chun Meng (Journal of Environmental Management, 2026)

Theta-aurora dynamics: Ionospheric mapping of evolving magnetospheric plasma boundaries - Xin-Ming Chen; Zan-Yang Xing; Qing-He Zhang; Yong-Liang Zhang; Hui-Gen Yang; L. R. Lyons; K. Oksavik; S. E. Milan; Rui-Long Guo; Tong Xu; Bin-Bin Tang; Xiang-Yu Wang; et al. (Science China Earth Sciences, 2026)
The theta-aurora, an auroral feature bridging the nightside and dayside auroral oval under a northward interplanetary magnetic field (IMF), is closely linked to the energetic plasma evolving within the magnetosphere. While existing views emphasize that energetic plasma resides on closed field lines, the mechanism by which it is accelerated and precipitates on open field lines to form the theta aurora remains poorly understood. Here, we introduce a mechanism derived from multi-instrument observations of theta-aurora evolution in the Northern Hemisphere and simulations conducted using a global magnetohydrodynamics (MHD) model. The observations and simulations exhibit excellent agreement, revealing that the theta-aurora represents ionospheric projections of boundaries between distinct magnetospheric plasma. These different magnetospheric plasma, an energetic structure originating from the plasma sheet and the preexisting cold lobe plasma, develop a boundary with contrasting physical properties that drive localized plasma instabilities. Particle precipitation occurs at plasma boundary, and controls both the formation and temporal evolution of theta-aurora. Our findings provide critical insights into the coupling between the ionosphere and magnetosphere under northward IMF.

Wolframite and cassiterite geochemistry deciphers W–Sn ore formation: A case study from the Zuoba quartz-vein tungsten deposit, South China - Kai-Han Zhang; Jun-Yi Pan; Pei Ni; Gen-Wen He; Lin-Lin Peng; Ming-Sen Fan; Yuan-Long Zhang; Wen-Sheng Li (Journal of Asian Earth Sciences, 2026)

Seismic data processing key technology for coalbed methane reservoir - Ming Zhang; Bao-yin Zhao; Zhi-fang Ran; Wen-wu Shi; Hao Li; Kai-long Wu; Gen-yang Tang (Applied Geophysics, 2026)

Machine learning-driven parameter calibration for the FDEM model in weathered rock seabed - Bo Han; Chun-lei Zhang; Gen-qiang Peng; Zhi-shuai Zhang; Yun-long Tie; Bo-nan Zhang (Marine Georesources & Geotechnology, 2026)

Curcumin-mediated photodynamic action disturbs TOM70-depedent MIC60 import to damage mitonchondria against breast cancer - Xiang-Yi Zhao; Min Yan; Liang Zheng; Chang-Long Gou; Qi Huang; Liu-Gen Li; Xin-Ran Yu; Jing-Yu Lu; Cui Hu; Si-Han Zhang; Cunqing Kong; Fan Leng; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

A new insight into the mechanism of DEHP-induced cardiotoxicity: Triggering pyroptosis of cardiomyocytes by disrupting sphingolipid metabolism - Jia-Gen Cui; Hao Zhang; Yue-Qi Zhang; Bing Sun; Xue-Nan Li; Yi Zhao; Jin-Long Li (Journal of Hazardous Materials, 2025)

Ultraviolet assisted defects engineering of metal organic frameworks towards high performance oxygen evolution reaction - Rana Sami Ul Haq; Zhihao Lei; Shuai Qi; Muhammad Ibrar Ahmed; Vibin Perumalsamy; Yitong Cao; Kavitha Ramadass; Binodhya Wijerathne; Xun Geng; Sohail Ahmed; Long Hu; Liang Qiao; et al. (Chemical Engineering Journal, 2025)

Integrating methane conversion with multi-pathway nitrogen removal for wastewater in membrane-enabled stratified biofilm: System development and microbial dynamics - Chun-Yan Yuan; Yu-Xia; Jia-Hao Huo; Cai-Long Nie; Ke-Xin Zhang; Liang-Feng; Xiao-Li Su; Zi Song; Gen-Ping Yi; Fei-Yun Sun (Bioresource Technology, 2025)

Optimizing agricultural management practices to promote ratoon rice yield during ratoon crop: A comprehensive global meta-analysis - Shi-Wen Deng; Yousif Abdelrahman Yousif Abdellah; Hong-Yu Chen; Ping-Lei Gao; Mutaz Mohammed Abdallah; Muhammad Shoaib Rana; Fu-Qiang Yu; Qi-Gen Dai; Rui-Long Wang (Field Crops Research, 2025)

Numerical investigation of shear effects between seafloor sediment and grousers of deep-sea mining vehicles: a comparison of bionic buffalo hoof grousers and straight grousers - Gen Li; Junlin Zhao; Manhong Li; Xuguang Chen; Zhou Li; Andi Yu; Cong Ding; Zhongtao Wang; Long Yu (Ocean Engineering, 2025)

Calcium homeostasis imbalance mediates DEHP induced mitochondrial damage in cerebellum and the antagonistic effect of lycopene - Jia-Gen Cui; Hao Zhang; Ming-Shan Chen; Jia-Xin Wang; Yi Zhao; Jin-Long Li (Science of The Total Environment, 2024)

Rapamycin protects mouse skin from ultraviolet B-induced photodamage by modulating Hspb2-mediated autophagy and apoptosis - Ang Li; Ai-Jun Chen; Jing Xu; Zhu-Yuan Wen; Gen-Long Bai; Zi-Yue Wang; Yu-Xin Jiang; Ping Wang (Molecular Biology Reports, 2024)

The material-structure duality in rock mass failure and instability: Concept, unified numerical scheme, and benchmark - Shiguo Feng; Gen Li; Long Zheng (Computers and Geotechnics, 2024)

Triple-function eutectic solvent additive for high performance lithium metal batteries - Wenqiang Fang; Zuxin Wen; Fenglin Wang; Long Chen; Ying Zhang; Ning Zhang; Xiaohe Liu; Gen Chen (Science Bulletin, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Expressions of electron escape probability and photo-emission from metals - Yi-Fan Liu; Ai-Gen Xie; Jing Tang; Hong-Jie Dong; Yun-Long Xie (Annals of Nuclear Energy, 2023)

PMS activation by hollow sulfur doped multilayer carbon shell wrapped CoFe alloy: Confined adsorption and surface activation - Xinxin Long; Chuanping Feng; Meng Liu; Xiaoping Li; Zonghan Huang; Yuxuan Du; Yang Chen; Shengjiong Yang; Gen Wang; Dahu Ding; Wenli Huang; Rongzhi Chen (Journal of Cleaner Production, 2023)

Effects of superficial gas velocity on the performance of an air-lift internal circulation partial nitrification-anammox granular sludge reactor - Xu Zhang; Wei-Qi Zhao; Gen-Ji Yao; Jin-Long Zhuang; Hong Liu; Hui-Jie Gao; Yong-Di Liu; Wei Li (Chemosphere, 2023)

Quantum oscillations in field-induced correlated insulators of a moiré superlattice - Le Liu; Yanbang Chu; Guang Yang; Yalong Yuan; Fanfan Wu; Yiru Ji; Jinpeng Tian; Rong Yang; Kenji Watanabe; Takashi Taniguchi; Gen Long; Dongxia Shi; et al. (Science Bulletin, 2023)

Reliable spectroscopic identification of minerals associated with serpentinization: Relevance to Mars exploration - Wen-Ping Liu; Wei Yin; Bin-Long Ye; Tian-Lei Zhao; Qi-Zhi Yao; Yi-Liang Li; Sheng-Quan Fu; Gen-Tao Zhou (Icarus, 2023)

Azospirillum Aestuarii sp. nov., a Novel Nitrogen-Fixting and Aerobic Denitrifying Bacteria Isolated from an Estuary of a Freshwater River - Can-Hai Xu; Gen Chen; Yan Liu; Wei Xiao; Xiao-Long Cui; Zhang-Gui Ding; Wei-Hong Liu; Yong-Xia Wang (Current Microbiology, 2023)

Comprehensive understanding of DOM reactivity in anaerobic fermentation of persulfate-pretreated sewage sludge via FT-ICR mass spectrometry and reactomics analysis - Jibao Liu; Chenlu Wang; Zhineng Hao; Gen Kondo; Manabu Fujii; Qing-Long Fu; Yuansong Wei (Water Research, 2023)

Heme-oxygenase-1 as a target for phthalate-induced cardiomyocytes ferroptosis - Jia-Xin Wang; Yi Zhao; Ming-Shan Chen; Hao Zhang; Jia-Gen Cui; Jin-Long Li (Environmental Pollution, 2023)

Anionic metal-organic framework modified separator boosting efficient Li-ion transport - Jiaqi Li; Long Chen; Fengling Wang; Zuoyu Qin; Ying Zhang; Ning Zhang; Xiaohe Liu; Gen Chen (Chemical Engineering Journal, 2023)

Interdecadal change in the influence of El Niño in the developing stage on the central China summer precipitation - Lin Chen; Gen Li; Shang-Min Long; Chujie Gao; Zhiyuan Zhang; Bo Lu (Climate Dynamics, 2022)

The role of earthquake-induced landslides in erosion and weathering from active mountain ranges: Progress and perspectives - Zhangdong Jin; Robert G. Hilton; A. Joshua West; Gen K. Li; Fei Zhang; Jin Wang; Gaojun Li; Xuanmei Fan; Meng-Long Hsieh (Science China Earth Sciences, 2021)

Carbon storage of the forest and its spatial pattern in Tibet, China - Long-yu Jia; Gen-xu Wang; Ji Luo; Fei Ran; Wei Li; Jun Zhou; Dan-li Yang; Wen-bo Shi; Qian Xu; Kun Zhu; Yang Yang (Journal of Mountain Science, 2021)

Surface Temperature Changes Projected by FGOALS Models under Low Warming Scenarios in CMIP5 and CMIP6 - Shang-Min Long; Kai-Ming Hu; Gen Li; Gang Huang; Xia Qu (Advances in Atmospheric Sciences, 2021)

Land–atmosphere interaction over the Indo-China Peninsula during spring and its effect on the following summer climate over the Yangtze River basin - Chujie Gao; Haishan Chen; Gen Li; Hedi Ma; Xinyu Li; Shangmin Long; Bei Xu; Xing Li; Xinmin Zeng; Hong Yan; Ziqian Wang; Song Yang (Climate Dynamics, 2019)

Avian influenza viruses (AIVs) H9N2 are in the course of reassorting into novel AIVs - Hui-ping Chang; Li Peng; Liang Chen; Lu-fang Jiang; Zhi-jie Zhang; Cheng-long Xiong; Gen-ming Zhao; Yue Chen; Qing-wu Jiang (Journal of Zhejiang University-SCIENCE B, 2018)

Evolution of drug-resistant mutations in HBV genomes in patients with treatment failure during the past seven years (2010–2016) - Hong-yu Zhang; Long-gen Liu; Chun-yan Ye; Chun-hua Chen; Shuang-xiong Hang; Zhen Zhu; Hong-yu Shen; Ze-yu Huang; Wen-yi Chen; Yuan Xue (Virus Genes, 2018)

Puerarin-7-O-glucuronide, a water-soluble puerarin metabolite, prevents angiotensin II-induced cardiomyocyte hypertrophy by reducing oxidative stress - Ning Hou; Bin Cai; Cai-Wen Ou; Zhen-Hui Zhang; Xia-Wen Liu; Mu Yuan; Gan-Jian Zhao; Shi-Ming Liu; Long-Gen Xiong; Jian-Dong Luo; Cheng-Feng Luo; Min-Sheng Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

The anxiolytic- and antidepressant-like effects of ATPM-ET, a novel κ agonist and μ partial agonist, in mice - Qian Wang; Yu Long; Ai Hang; Gui-Ying Zan; Xiao-Hong Shu; Yu-Jun Wang; Jing-Gen Liu (Psychopharmacology, 2016)

Steady-state and dynamic photosynthetic performance and nitrogen partitioning in the shade-demanding plant Panax notoginseng under different levels of growth irradiance - Jun-Wen Chen; Shuang-Bian Kuang; Guang-Qiang Long; Zeng-Gui Meng; Long-Gen Li; Zhong-Jian Chen; Guang-Hui Zhang; Sheng-Chao Yang (Acta Physiologiae Plantarum, 2014)

A method developed for determination of heptachlor and its metabolites from pork - Hai Gen Zuo; Jian Xin Zhu; Chun Rui Zhan; Guo Yan Tang; Ping Guo; Yuan Long Wei; Hai Long Zeng; Hong Yang (Environmental Monitoring and Assessment, 2014)

Erratum to: UDP-glucuronosyltransferase 1A1 is the principal enzyme responsible for puerarin metabolism in human liver microsomes - Cheng-Feng Luo; Bin Cai; Ning Hou; Mu Yuan; Shi-Ming Liu; Hong Ji; Long-Gen Xiong; Wei Xiong; Jian-Dong Luo; Min-Sheng Chen (Archives of Toxicology, 2012)

UDP-glucuronosyltransferase 1A1 is the principal enzyme responsible for puerarin metabolism in human liver microsomes - Cheng-Feng Luo; Bin Cai; Ning Hou; Mu Yuan; Shi-Ming Liu; Hong Ji; Long-Gen Xiong; Wei Xiong; Jian-Dong Luo; Min-Sheng Chen (Archives of Toxicology, 2012)

Evaluation of M307 of FUT1 gene as a genetic marker for disease resistance breeding of sutai pigs - Wen-bin Bao; Lan Ye; Jing Zhu; Zhang-yuan Pan; Guo-qiang Zhu; Xue-gen Huang; Sheng-long Wu (Molecular Biology Reports, 2012)

The effect of mutation at M307 in FUT1 gene on susceptibility of Escherichia coli F18 and gene expression in Sutai piglets - Wen-bin Bao; Lan Ye; Zhang-yuan Pan; Jing Zhu; Zi-Dong Du; Guo-qiang Zhu; Xue-gen Huang; Sheng-long Wu (Molecular Biology Reports, 2012)

Erratum to: The effect of mutation at M307 in FUT1 gene on susceptibility of Escherichia coli F18 and gene expression in Sutai piglets - Wen-bin Bao; Lan Ye; Zhang-yuan Pan; Jing Zhu; Zi-Dong Du; Guo-qiang Zhu; Xue-gen Huang; Sheng-long Wu (Molecular Biology Reports, 2012)

Induction of Mitogynogenetic Diploids and Identification of WW Super-female Using Sex-Specific SSR Markers in Half-Smooth Tongue Sole (Cynoglossus semilaevis) - Song-Lin Chen; Xiang-Shan Ji; Chang-Wei Shao; Wen-Long Li; Jing-Feng Yang; Zuo Liang; Xiao-Lin Liao; Gen-Bo Xu; Ying Xu; Wen-Tao Song (Marine Biotechnology, 2012)

Timing, Conditions, and Complications of Post-operative Conception and Pregnancy in Female Renal Transplant Recipients - Long-gen Xu; Shu Han; Yong Liu; Hong-wei Wang; Yi-rong Yang; Feng Qiu; Wan-ling Peng; Li-gong Tang (Cell Biochemistry and Biophysics, 2011)

Beneficial genotype of swine FUT1 gene governing resistance to E. coli F18 is associated with important economic traits - WEN-BIN BAO; LAN YE; ZHANG-YUAN Pan; JIN ZHU; GUO-QIANG ZHU; XUE-GEN HUANG; SHENG-LONG WU (Journal of Genetics, 2011)

Genetic differentiation and phylogeographical structure of the Brachionus calyciflorus complex in eastern China - XIAN‐LING XIANG; YI‐LONG XI; XIN‐LI WEN; GEN ZHANG; JIN‐XIA WANG; KE HU (Molecular Ecology, 2011)
Spatio‐temporal patterns and processes of genetic differentiation in passively dispersing zooplankton are drawing much attention from both ecologists and evolutionary biologists. Two opposite phylogeographical scenarios have already been demonstrated in rotifers, which consist of high levels of genetic differentiation among populations even on small geographical scales on the one hand and the traditionally known cosmopolitanism that is associated with high levels of gene flow and long‐distance dispersal via diapausing stages on the other hand. Here, we analysed the population genetic structure and the phylogeography of the Brachionus calyciflorus species complex in eastern China. By screening a total of 318 individuals from ten locations along a 2320‐km gradient and analysing samples from two growing seasons, we aimed at focusing on both small‐ and large‐scale patterns. We identified eight cryptic species and verified species status of two of these by sexual reproduction tests. Samples in summer and winter yielded different cryptic species. The distribution patterns of these genetically distinct cryptic species were diverse across eastern China, from full cosmopolitanism to local endemism. The two most abundant cryptic species BcWIII and BcSW showed a pattern of strong genetic differentiation among populations and no significant isolation by distance. Long‐distance colonization, secondary contact and recent range expansion are probably responsible for the indistinct pattern of isolation by distance. Our results suggest that geographical distance is more important than temporal segregation across seasons in explaining population differentiation and the occurrence of cryptic species. We explain the current phylogeographical structure in the B. calyciflorus species complex by a combination of recent population expansion, restricted gene flow, priority effects and long‐distance colonization.

Antitumor and antimicrobial activities of endophytic fungi from medicinal parts of Aquilaria sinensis - Jin-long Cui; Shun-xing Guo; Pei-gen Xiao (Journal of Zhejiang University-SCIENCE B, 2011)

Comparative analysis of rotifer community structure in five subtropical shallow lakes in East China: role of physical and chemical conditions - Xin-Li Wen; Yi-Long Xi; Fang-Ping Qian; Gen Zhang; Xian-Ling Xiang (Hydrobiologia, 2011)

In vitro induction of inflorescence in Dioscorea zingiberensis - Xiao-Long Huang; Bo Yang; Chun-Gen Hu; Jia-Ling Yao (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

Forecasting Up to Year 2000 on Shanghai's Environmental Quality - Long Gen Ying; Hsiang-Te Kung (Environmental Monitoring and Assessment, 2000)